2017
DOI: 10.3892/ol.2017.6826
|View full text |Cite
|
Sign up to set email alerts
|

Renin angiotensin system deregulation as renal cancer risk factor (Review)

Abstract: For numerous years, the non-cardiovascular role of the renin-angiotensin system (RAS) was underestimated, but recent studies have advanced the understanding of its function in various processes, including carcinogenesis. Numerous evidence comes from preclinical and clinical studies on the use of antihypertensive agents targeting the RAS, including angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers. It has been demonstrated that the use of ACEIs can alter the incidence of renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 77 publications
(112 reference statements)
0
70
0
3
Order By: Relevance
“…The prior published data have demonstrated an association between Ang II and cancer development (22,23). Penafuerte et al (24) revealed that Ang II is a major upstream regulator of cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…The prior published data have demonstrated an association between Ang II and cancer development (22,23). Penafuerte et al (24) revealed that Ang II is a major upstream regulator of cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, this area has not been extensively studied and requires further investigation. Others have investigated whether blocking the RAS can either change the incidence of tumours or positively affect tumour treatment 79,80 . Given the large number of different tumours and tumour treatments, this is still an evolving area of investigation.…”
Section: Ace In the Immune Systemmentioning
confidence: 99%
“…Performance specification of RAS thus comes to evolve in terms of pathways of metabolism and also of cell survival and cell death pathway evolution. The use of antihypertensive agents targeting RAS, including angiotensin-converting enzyme inhibitors and angiotensin receptor blockers can alter the incidence of renal cell carcinoma and also prolong patient survival [13] . It is further in terms of incremental activation that targeting pharmaceutics performs the significant roles for further transformation and this within a global scenario of cancer lesion maintenance.…”
Section: Internal Membranesmentioning
confidence: 99%